Effects of exercise on cardiac autonomic modulation in children: literature update - Mondoni, Gustavo Henrique De Oliveira; Vanderlei, Luiz Carlos Marques; Saraiva, Bruno; Vanderlei, Franciele Marques (Pontifícia Universidade Católica do Paraná, 2015)
AbstractIntroduction It is known that physical exercise is beneficial and precipitates adjustments to the autonomic nervous system. However, the effect of exercise on cardiac autonomic modulation in children, despite its importance, is poorly investigated.Objective To bring together current information about the effects of exercise on heart rate variability in healthy and obese children.Methods The literature update was performed through a search for articles in the following databases; PubMed, PEDro, SciELO and Lilacs, using the descriptors “exercise” and “child” in conjunction with the descriptors “autonomic nervous system”, “sympathetic nervous system”, “parasympathetic nervous system” and also with no descriptor, but the key word of this study, “heart rate variability”, from January 2005 to December 2012.Results After removal of items that did not fit the subject of the study, a total of 9 articles were selected, 5 with healthy and 4 with obese children.Conclusion The findings suggest that exercise can act in the normalization of existing alterations in the autonomic nervous system of obese children, as well as serve as a preventative factor in healthy children, enabling healthy development of the autonomic nervous system until the child reaches adulthood.

ResumoIntrodução Sabe-se que a prática de exercícios físicos é benéfica e proporciona adaptações ao sistema nervoso autônomo. No entanto, o efeito do exercício sobre a modulação autonômica cardíaca em crianças, apesar de ser uma condição importante, é pouco investigada.Objetivo Reunir informações atuais a respeito dos efeitos do exercício físico sobre a variabilidade da frequência cardíaca de crianças saudáveis e obesas.Método A atualização da literatura foi realizada por meio de uma busca dos artigos nas bases de dados PubMed, PEDro, Scielo e Lilacs — por meio dos descritores “exercício” e “criança” em cruzamento com os descritores “sistema nervoso autônomo”, “sistema nervoso simpático”, “sistema nervoso parassimpático” e também com o não descritor, mas palavra chave deste estudo, “variabilidade da frequência cardíaca” — publicados no período de janeiro de 2005 a dezembro de 2012.Resultados Após a eliminação dos artigos que não se enquadravam no tema do artigo foi selecionado um total de nove artigos, sendo cinco com crianças saudáveis e quatro com obesas.Conclusão Os achados sugerem que o exercício físico pode atuar na normalização das alterações existentes no sistema nervoso autonômico de crianças obesas, assim como servir como um fator de prevenção em crianças saudáveis, para que ocorra um desenvolvimento saudável do sistema nervoso autonômico até que a crianças atinja a idade adulta.
Efeitos do exercício sobre a modulação autonômica em crianças: atualização de literatura
Keywords: Physical exercise; Child; Heart rate variability; Autonomic nervous system; Exercício físico; Criança; Variabilidade da frequência cardíaca; Sistema nervoso autônomo